KNOWLEDGE AND USAGE OF THE SEVEN BASIC QUALITY CONTROL TOOLS BY PRODUCERS OF PRECAST CONCRETE PRODUCTS IN GHANA - Emmanuel ADINYIRA; Joshua AYARKWA; Isaac AIDOO (Journal of Construction Project Management and Innovation)
For very small organisations, the root cause of quality problems may be obvious, but once it gets beyond small businesses, most decision points and problem root causes will remain vague until valid data are studied and analysed. It is for such cases that quality management tools play an important role in helping improve the quality of products and processes. This research seeks to explore the level of knowledge and usage of the seven basic quality control tools by producers of precast concrete products in Ghana. A survey of 42 producers of precast concrete products in the cities of Accra and Tema was conducted to elicit the desired data. The data was basically analysed using gap and quadrant analyses. The study revealed very limited levels of both knowledge and usage of the said tools by these organisations even though their perception of quality was very good. Again, the survey identified some practical measures to help improve the quality of the operations of these organisations. Chief among these measures is training and education of the work force on the use of the seven basic quality control tools. Even though the findings are limited to data from only two cities, they tend to support earlier findings from similar studies, thus providing useful lessons for manufacturers of such products.